A novel biparatopic hybrid antibody-ACE2 fusion that blocks SARS-CoV-2 infection: implications for therapy. Issue 1 (1st January 2020) - Miao, Xiaoniu; Luo, Yi; Huang, Xi; Lee, Suki M. Y.; Yuan, Zhijun; Tang, Yongzhou; Chen, Liandi; Wang, Chao; Wu, Fan; Xu, Yifeng; Jiang, Wenchao; Gao, Wei; et al.
ABSTRACT: In the absence of a proven effective vaccine preventing infection by SARS-CoV-2, or a proven drug to treat COVID-19, the positive results of passive immune therapy using convalescent serum provide a strong lead. We have developed a new class of tetravalent, biparatopic therapy, 89C8-ACE2. It combines the specificity of a monoclonal antibody (89C8) that recognizes the relatively conserved N-terminal domain of the viral Spike (S) glycoprotein, and the ectodomain of ACE2, which binds to the receptor-binding domain of S. This molecule shows exceptional performance in vitro, inhibiting the interaction of recombinant S1 to ACE2 and transduction of ACE2-overexpressing cells by S-pseudotyped lentivirus with IC50s substantially below 100 pM, and with potency approximately 100-fold greater than ACE2-Fc itself. Moreover, 89C8-ACE2 was able to neutralize authentic viral infection in a standard 96-h co-incubation assay at low nanomolar concentrations, making this class of molecule a promising lead for therapeutic applications.